Application of a mindfulness and compassion‐based approach to the at‐risk mental state. (5th July 2017) - Hickey, Tara; Nelson, Barnaby; Meadows, Graham
Abstract: Background: Psychological interventions based on mindfulness and compassion approaches have demonstrated improved outcomes across a range of disorders. However, the application of these approaches to the at‐risk mental state (ARMS) has received little attention to date. This paper explores their potential to enhance treatment of the ARMS. Methods: This article follows guidelines developed by the UK Medical Research Council and the US National Institute of Health on developing and evaluating complex interventions. The paper (1) describes the ARMS, treatment and outcomes, (2) explores relevant literature on mindfulness and compassion, (3) discusses the likely processes of change involved in a mindful compassionate approach, (4) provides a rationale for integrating mindfulness and compassion into treatment of the ARMS, and (5) offers recommendations to enhance knowledge and treatment in this area. Results: Common ARMS experiences include attenuated psychotic symptoms, depression, anxiety, insecure attachment style, and difficulties with daily functioning. In particular, voice tones are often hostile or critical and paranoia is associated with a self‐attacking inner dialogue. Mindfulness and compassion are emotion regulation strategies that have the potential to tone down these threatening experiences by enhancing a sense of safety and reassurance. However, the potential impact of mindfulness and compassion on attachment style and feelings of social connectedness warrants further investigation. Conclusions: Mindfulness and compassion approaches are unique strategies that have the potential to significantly advance treatment of the ARMS. It is timely that a mindfulness and compassion‐based intervention for the ARMS is developed and evaluated according to best practice guidelines. Abstract :